Characterizing the Sources of Pharmacokinetic Variability for TAK‐117 (Serabelisib), an Investigational Phosphoinositide 3‐Kinase Alpha Inhibitor: A Clinical Biopharmaceutics Study to Inform Development Strategy. Issue 5 (31st August 2018) - Patel, Chirag G.; Rangachari, Lakshmi; Patti, Mark; Griffin, Celina; Shou, Yaping; Venkatakrishnan, Karthik
Abstract: TAK‐117 (also known as MLN1117 or serabelisib) is an orally available inhibitor of phosphoinositide 3‐kinase alpha being developed for treatment of solid tumors. This clinical study in healthy subjects assessed the relative bioavailability of a TAK‐117 tablet compared with a capsule formulation (part 1) and the effect of food (part 2) and intragastric pH modulation (part 3) on TAK‐117 pharmacokinetics. In part 1, subjects received single doses of 900 mg TAK‐117 under fasting conditions as capsules and tablets on 2 different occasions in random order. In part 2, subjects received a single dose of 600 mg TAK‐117 under fed (high‐fat meal) or fasted conditions on 2 different occasions in random order. In part 3, subjects received a single dose of 900 mg TAK‐117 alone and in combination with lansoprazole in a fixed sequence. Blood samples were collected up to 72 hours after each TAK‐117 dose. The geometric mean ratios (90% confidence intervals) for the area under the TAK‐117 plasma concentration‐time curves were 1.53 (0.93‐2.51) for tablets versus capsules, 1.50 (1.00‐2.25) for fed versus fasted, and 0.02 (0.01‐0.04) for TAK‐117 plus lansoprazole compared with TAK‐117 alone. The most common adverse event was nausea, the incidence of which was reduced when TAK‐117 was administered with food despite the increased systemic exposure. The incidence of all adverse events was reduced when TAK‐117 was administered with lansoprazole, which was consistent with the substantial reduction in bioavailability. Intersubject variability of TAK‐117 was high. Careful management of intragastric pH‐modulatory concomitant medications and food intake may be required.